Simulating and optimizing compound refractive lens‐based X‐ray microscopes. (20th February 2017) - Simons, Hugh; Ahl, Sonja Rosenlund; Poulsen, Henning Friis; Detlefs, Carsten
Abstract : A comprehensive ray‐transfer matrix formalism for the use and design of compound refractive lens‐based X‐ray microscopes is presented, including closed analytical expressions for key optical parameters. These form the basis of an optimization, which reveals that thick‐lens imaging geometries are ideal in terms of spatial resolution and achromaticity. Abstract : A comprehensive optical description of compound refractive lenses (CRLs) in condensing and full‐field X‐ray microscopy applications is presented. The formalism extends ray‐transfer matrix analysis by accounting for X‐ray attenuation by the lens material. Closed analytical expressions for critical imaging parameters such as numerical aperture, spatial acceptance (vignetting), chromatic aberration and focal length are provided for both thin‐ and thick‐lens imaging geometries. These expressions show that the numerical aperture will be maximized and chromatic aberration will be minimized at the thick‐lens limit. This limit may be satisfied by a range of CRL geometries, suggesting alternative approaches to improving the resolution and efficiency of CRLs and X‐ray microscopes.